If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 = 6r + 3 Reorder the terms: 33 = 3 + 6r Solving 33 = 3 + 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. 33 + -6r = 3 + 6r + -6r Combine like terms: 6r + -6r = 0 33 + -6r = 3 + 0 33 + -6r = 3 Add '-33' to each side of the equation. 33 + -33 + -6r = 3 + -33 Combine like terms: 33 + -33 = 0 0 + -6r = 3 + -33 -6r = 3 + -33 Combine like terms: 3 + -33 = -30 -6r = -30 Divide each side by '-6'. r = 5 Simplifying r = 5
| (2-w)(4w-7)=0 | | 5x-8y=-18 | | cos^(2)x-7/2cos(x)-2 | | ((z^(4/3))(y^(-3)))^(1/4) | | 5s+4t-2s-(-3t)= | | 4.75d=.07d^3/2 | | n-24=8 | | 99g-1=98 | | 22=29x+4 | | -5x-2=Y | | ytjg+7981=12345 | | 5x-60+8x-120=x-60 | | ytjg+7981=12345g | | 2x+3x+5=37 | | 2x-5(1-x)=1-3(1-2x) | | y=-2(x-5)(x-9) | | 7x+1+8x= | | 5x-6=3(2x-1)+8 | | 5x+196=13x-12 | | t(y)=36(10)-045y | | 8a+6-11=11 | | 3x-12=x-4 | | 70=6+x | | 15y+3=-36-18 | | ln(t+8)+ln(t-1)-1=0 | | 56-4x=5x+24 | | 1+2(7x-7)=-14 | | 12x=-47+107 | | 6-10x=66-31x | | 2m+9=29 | | 8x-30=-6(x-9) | | -7u-2=5u^2 |